Evaluating the Effects of Metalinguistic and Working Memory Training on Reading Fluency in Chinese and English: A Randomized Controlled Trial - Siu, Tik-Sze Carrey; McBride, Catherine; Tse, Chi-Shing; Tong, Xiuhong; Maurer, Urs (Frontiers in Psychology, 2018)
Children traditionally learn to read Chinese characters by rote, and thus stretching children’s memory span could possibly improve their reading in Chinese. Nevertheless, 85% of Chinese characters are semantic-phonetic compounds that contain probabilistic information about meaning and pronunciation. Hence, enhancing children’s metalinguistic skills might also facilitate reading in Chinese. In the present study we tested whether training children’s metalinguistic skills or training their working-memory capacity in eight weeks would produce reading gains, and whether these gains would be similar in Chinese and English. We recruited 35 second graders in Hong Kong and randomly assigned them to a metalinguistic training group (N = 13), a working-memory training group (10), or a waitlist control group (12). In the metalinguistic training, children were taught to analyze novel Chinese characters into phonetic and semantic radicals and novel English words into onsets and rimes. In the working-memory training, children were trained to recall increasingly long strings of Cantonese or English syllables in correct or reverse order. All children were tested on phonological skills, verbal working memory, and word reading fluency in Chinese and in English before and after training. Analyses of the pre- and post-test data revealed that only the metalinguistic training group, but not the other two groups, showed significant improvement on phonological skills in Chinese and English. Working-memory span in Chinese and English increased from the pre- to post-test in the working-memory training group relative to other two groups. Despite these domain-specific training effects, the two training groups improved similarly in word reading fluency in Chinese and English compared to the control group. Our findings suggest that increased metalinguistic skills and a larger working-memory span appear equally beneficial to reading fluency, and that these effects are similar in Chinese and English.